Developing a Conceptual Model of Cultural Policy-making in District 8 Payame Noor Universities based on Piety - Shahabi Nejad, Fatemeh (2020)
The present study aimed to provide a conceptual model of cultural policy-making in Payame Noor universities in District 8 based on piety and virtue. In this study, the components of cultural policy based on piety were first identified through exploratory studies and surveys of knowledge-aware experts using the Delphi technique, and then these factors were tested in the form of a model designed in the statistical population. The statistical population of the study was 30 experts to test the model and to measure the research variables according to the managers of District 8 Payame Noor University; the head of cultural affairs of the university and clerics and professors of Islamic education department of Payame Noor Universities District 8 were used, which were 110 individuals. Due to the limited statistical population, the census method was used. The present study is a descriptive-correlational research that has been done by survey method. Furthermore, this research is development-applied in terms of purpose. The data collection method in this study is a combination of library and field studies and the tools of data collection are review of documents, interviews and questionnaires, which confirmed the validity and reliability of the questionnaires. In order to analyze the data, descriptive statistics (types of indicators, statistical tables and graphs) and inferential statistics (structural equation modeling) have been used. The research findings, while confirming the proposed model of research, showed that piety and its components: God-centeredness and monotheism, promoting the need to obey divine sovereignty, expediency in Islamic culture and meritocracy (Imam Ali's biography) have a positive and significant effect on cultural planning. At the end, research suggestions were presented.